Old Wine in New Bottles: Evolutionary Debunking Arguments and the Benacerraf-Field Challenge - Klenk, Michael (Ethical theory and moral practice, 2017)
Evolutionary debunking arguments (EDAs) purport to show that robust moral realism, the metaethical view that there are non-natural and mind-independent moral properties and facts that we can know about, is incompatible with evolutionary explanations of morality. One of the most prominent evolutionary debunking arguments is advanced by Sharon Street, who argues that if moral realism were true, then objective moral knowledge is unlikely because realist moral properties are evolutionary irrelevant and moral beliefs about those properties would not be selected for. However, no evolutionary, causal explanation plays an essential role in reaching the arguments epistemological conclusion. Streets argument depends on the Benacerraf-Field challenge, which is the challenge to explain the reliability of our moral beliefs about causally inert moral properties. The Benacerraf-Field challenge relies on metaphysically necessary facts about realist moral properties, rather than on contingent Darwinian facts about the origin of our moral beliefs. Attempting to include an essential causal empirical premise yet avoiding recourse to the Benacerraf-Field problem yields an argument that is either self-defeating or of limited scope. Ultimately, evolutionary, causal explanations of our moral beliefs and their consequences do not present the strongest case against robust moral realism. Rather, the question is whether knowledge of casually-inert, mind-intendent properties is plausible at all.